A comparative evaluation of proximate composition, elemental profiling and oil physicochemical properties of black cumin (Nigella sativa L.) seeds and argan (Argania spinosa L. Skeels) kernels - Oubannin, Samira; Bijla, Laila; Gagour, Jamila; Hajir, Jawad; Aabd, Naima Ait; Sakar, El Hassan; Salama, Mohamed Abdelbaset; Gharby, Said (Chemical Data Collections, 2022)
In this data article, proximate composition, elemental profiling of fruits and oil cakes and the physicochemical properties of the mechanically extracted oil of Moroccan black cumin and argan were compared. Oxidative stability was determined under accelerated aging conditions at 60°C for four months. Elemental profiling showed comparable values for nigella seeds, argan kernels and their oil cakes. The highest values of oil content (52%) and energy value (595.14 kcal/100 g) were found in argan kernels, the argan cake also showed its superiority in terms of moisture content (6.46%) and protein content (45.93%). The highest carbohydrate content (51.31%) was found in black cumin cake. Black cumin (cake and oil) can be considered as valuable sources for new multipurpose products for industrial, food and cosmetic use. Oil oxidation outcomes revealed sensitity of black cumin oil as compared to argan oil. Therefore, special care should be considered for its prolonged storage. [Display omitted]